ORGANISATIONAL SUPPORT AND COMMITMENT ON EMPLOYEES' JOB SATISFACTION OF FORESTRY RESEARCH INSTITUTE OF NIGERIA - Olaoluwa Ayodeji ADEBAYO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this study is to examine and determine the hotel guests’ perception, experience and satisfaction of waiting for service. This study proposes that there is a significant effect of guests’ perception and experience on their satisfaction of waiting for hotel services. For this purpose, a detailed literature review was examined. Furthermore, 245 questionnaire was applied to 7 hotels guests above the age of 18 in Ado-Ekiti, Nigeria through a simple random sample selection technique to test their perception, experience and satisfaction of waiting for hotel services scales. Variables related to the survey participants and their relation to each other were tested by linear regression analysis and it was understood that there was a significant relationship between these factors. According to the result of linear regression analysis, it was observed that there was a significant positive relationship between guests' satisfaction vis-à-vis their perception (β=0.677) and experience (β=0.253) of waiting for service.